Clients' Perspectives on Quality of Delivery Services in a Rural Setting in Tanzania: Findings from a Qualitative Action-Oriented Research - Gerald J. Makuka, MD; Moses M. Sango, MD; Ayubu E. Mashambo, MD; Abednego E. Mashambo, MD; Sia E Msuya, MD, PhD; Sabina P Mtweve, MD, MSc (Global Health and Education Projects, Inc., 2017)
Objective: To know and understand the perspectives of women on the quality of maternal health services provided at their health facility (HF) and to incite community self-propelled problem identification and way forward. Methods: A qualitative action- oriented research was conducted in a rural setting in Tanzania from 2011 to 2014. Twenty In-Depth Interviews (IDIs) and two Focus Group Discussions were held. The IDIs were conducted with mothers who had attended antenatal care at the HF and delivered there. The recordings transformed into English texts were used for analysis to get themes and possible explanations that were compared and reflected. Results: More than half 60% of the respondents reported to have experienced abuse by the health staff, 80% reported lack of amenities and all agreed to unavailability of health services at odd hours or weekends. Conclusion and Global Health Implications: This study reveals that the quality of maternal health services provided at the HF is not up to standard. The study demonstrates the importance of self-diagnosis in a community and to propel self-community interventions towards improving rural health services. The government, researchers and other stakeholders have key roles in the elimination of health disparities and unhealthy political mingling in health care. Key words: Quality • Maternal Health • Qualitative • Action-Oriented Research • Rural Setting • Tanzania Copyright © 2017 Makuka et al. This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.